A modo de introducción del dossier «Cosmopolíticas y emancipación en América Latina» - Rueda Barrera, Eduardo A. (2024)
After exploring the practical-political meaning that underlies the idea of ​​“cosmopolitics” and describing its impact on the transformative agendas of Latin America, its links with cosmopolitanism are explained. At the end, the work of the Dossier is briefly reviewed.